Educator's blueprint: A how‐to guide for developing high‐quality multiple‐choice questions. Issue 1 (24th January 2023) - Gottlieb, Michael; Bailitz, John; Fix, Megan; Shappell, Eric; Wagner, Mary Jo
Abstract: Multiple‐choice questions are commonly used for assessing learners' knowledge, as part of educational programs and scholarly endeavors. To ensure that questions accurately assess the learners and provide meaningful data, it is important to understand best practices in multiple‐choice question design. This Educator's Blueprint paper provides 10 strategies for developing high‐quality multiple‐choice questions. These strategies include determining the purpose, objectives, and scope of the question; assembling a writing team; writing succinctly; asking questions that assess knowledge and comprehension rather than test‐taking ability; ensuring consistent and independent answer choices; using plausible foils; avoiding grouped options; selecting the ideal response number and order; writing high‐quality explanations; and gathering validity evidence before and evaluating the questions after use.